RESTRUCTURING IN THE OIL AND GAS INDUSTRY: IMPLICATIONS FOR HR PRACTITIONERS - Abbass, Isah Mohammed (European Scientific Journal, ESJ, 2012)
Management of people and organizations requires some specialist attributes. In managing these vital resources, there has to be a distinctive philosophy of providing and enhancing people-oriented organizational programmes. Restructuring is one of such activities or programmes. This activity is essentially designed to reconstruct or reorganize the structure of the business activities to suit objectives, purpose as well as circumstances of the job. Oil and gas industry is a potential sector of the business environment that is more prone to constant but periodic restructuring due to its dynamics. This Paper explores the structure and work environment in some oil and gas industry in attempts to reorganize or restructure them. These attempts are highlighted with implications for organizations’ employees, stakeholders as well as the HR Practitioners. An insight into the restructuring of PTI has been buttressed as a specific example on how the modern organizational perspectives have been put in place against the orthodox method in order to bring efficiency and effectiveness in the operational activities with resource centered HR Practitioners in focus.